Psychiatrists’ awareness of adherence to antipsychotic medication in patients with schizophrenia: results from a survey conducted across Europe, the Middle East, and Africa - Olivares, José Manuel (Dove Medical Press, 2013)
BACKGROUND: Nonadherence is common among patients with schizophrenia, although the rates vary according to means of assessment and patient population. Failure to adhere to medication can have a major impact on the course of illness and treatment outcomes, including increasing the risk of relapse and rehospitalization. Understanding psychiatrists’ perception of the causes and consequences of nonadherence is crucial to addressing adherence problems effectively. METHODS: The Europe, the Middle East, and Africa (EMEA) Spanish Adherencia Terapéutica en la Esquizofrenia (ADHES) survey was conducted by questionnaire during January–March 2010 among psychiatrists treating patients with schizophrenia in 36 countries. The survey comprised 20 questions. In addition to recording the demographic details of the 4722 respondents (~12% response rate), it canvassed their preferred methods of assessing adherence, their perceptions of adherence rates, reasons for nonadherence, and strategies to improve adherence. RESULTS: Psychiatrists estimated that 53% of their patients with schizophrenia were partially/nonadherent during the previous month. They estimated only one-third of patients who deteriorated after stopping medication were able to attribute this to nonadherence. Psychiatrists assessed adherence most often by patient interview. Lack of insight was viewed as the most important cause of medication discontinuation, followed by patients feeling better and thinking their medication unnecessary, and experiencing undesirable side effects. Considerably fewer psychiatrists viewed insufficient efficacy, cognitive impairment, or drug/alcohol abuse as the most important reasons for their patients stopping medication. CONCLUSION: Psychiatrists throughout EMEA recognize the impact of partial/nonadherence to medication, with patient enquiry being the most commonly used means of assessment. There remains a need for more proactive management of patients with schizophrenia, particularly in increasing patient insight of their illness in order to improve adherence and minimize the consequences of relapse. Strategies focused on raising awareness of the importance of adherence are also warranted, with the aim of improving patient outcomes in schizophrenia.